2021
DOI: 10.1111/iju.14748
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vesical Imaging–Reporting and Data System in predicting muscle‐invasive bladder cancer: A diagnostic meta‐analysis

Abstract: The objective of this study is to systematically evaluate the diagnostic performance of the Vesical Imaging–Reporting and Data System for predicting muscle‐invasive bladder cancer. Embase, PubMed and Web of Science were systematically searched from 1 September 2018 to 30 July 2021 to include proper studies. We included studies that included data on Vesical Imaging–Reporting and Data System and their associated pathological findings, and we assessed their quality using the Quality Assessment of Diagnostic Accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The Vesical Imaging-Reporting and Data System (VI-RADS) has been demonstrated to accurately predict muscle invasion of BCa before operation (48)(49)(50)(51). Although no correlation between CTCs/CECs and BCa stage was observed, the combination of VI-RADS and CTCs/CECs detecting may offer us a more valid judgment basis prior to surgery, particularly for patients with a VI-RADS score of 3.…”
Section: Discussionmentioning
confidence: 99%
“…The Vesical Imaging-Reporting and Data System (VI-RADS) has been demonstrated to accurately predict muscle invasion of BCa before operation (48)(49)(50)(51). Although no correlation between CTCs/CECs and BCa stage was observed, the combination of VI-RADS and CTCs/CECs detecting may offer us a more valid judgment basis prior to surgery, particularly for patients with a VI-RADS score of 3.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, encompassing 20 studies with 2725 patients, reported that VI-RADS achieved commendable performance in detecting muscle invasion status in bladder cancer. The pooled sensitivity and specificity of VI-RADS were reported as 0.82 and 0.95, respectively, when applying VI-RADS ≥ 4 [ 28 ]. Given the high specificity of VI-RADS ≥ 4, Taguchi, Satoru et al proposed a new algorithm based on VI-RADS for the management of bladder cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of disagreement between the two readers, consensus was reached through discussion. A meta-analysis has indicated that using VI-RADS ≥ 4 as a cutoff value yields high accuracy in evaluating muscular infiltration [ 28 ]. Consequently, tumors with a VI-RADS score of less than 4 on pre-NAC MRI were excluded from the present study.…”
Section: Methodsmentioning
confidence: 99%
“…However, because it is generally recommended that 4-mm-slices should be used for assessment, we mainly assessed these 4-mm images in the present study. We adopted a cutoff value of ≥ 4 for conventional VI-RADS because of its high specificity for the diagnosis of muscle invasion [ 31 ]. Negative NCE-VI-RADS was defined as a score of < 4 for both the T2WI and DWI categories, and positive NCE-VI-RADS was defined as a score of ≥ 4 for either of the T2WI or DWI categories (or both).…”
Section: Methodsmentioning
confidence: 99%